Effect of pasteurization and ripening temperature on chemical and sensory characteristics of traditional motal cheese - Rezaei, Ashkan; Alirezalu, Kazem; Damirchi, Sodeif Azadmard; Hesari, Javad; Papademas, Photis; Domínguez, Rubén; Lorenzo, José M.; Yaghoubi, Milad (My University, 2020)
The appropriate physicochemical and sensory characteristics and the traditional elaboration process of Motal cheese resulted in a high consumer acceptability. However, different process steps could have a significant effect on these characteristics. Thus, the present study aimed to investigate the effects of pasteurization, ripening time, and ripening temperature (6 °C and 12 °C) on the physicochemical properties, sensory characteristics, and proteolysis and lipolysis phenomenon of traditional Motal cheese. The cheeses were evaluated each 15 days during 3 months of ripening process. The results showed that pasteurization and ripening temperature had a significant effect on pH, acidity, dry matter, fat, protein, and salt (p < 0.05), which were higher in pasteurized cheeses ripened at higher temperature (12 °C). Moreover, the content of these parameters increased as ripening progressed. Proteolysis and lipolysis intensity were higher in the cheeses elaborated form raw milk and ripened at 12 °C (R12), mainly due to the higher activity of enzymes and/or bacteria. As a general conclusion, the pasteurization and low-temperature ripening process allows us to have a homogeneous product and ensure the microbiological stability of the cheeses, as well as presents higher physicochemical qualities than those obtained from raw milk.
Keywords: Motal cheese; Physicochemical parameters; Thermal treatment; Ripening process